Respuesta :

Answer =

[tex] = \frac{1}{y {}^{5} x {}^{2} } [/tex]

Step-by-step explanation:

Greetings !

simplify for variable y first

apply exponent rule

[tex]a {}^{b} .a {}^{c} = a {}^{b +c \\ } \\ y {}^{ - 8}y {}^{5} = y {}^{ - 8 + 3} [/tex]

Add/subtract the numbers -8+3=5

[tex] = y {}^{5} [/tex]

Apply exponent rule

[tex]a {}^{ - b} = \frac{1}{a {}^{b} } [/tex]

Thus,

[tex]y {}^{ - 5} = \frac{1}{y {}^{5} } [/tex]

secondly, simplify for the variable x

Apply exponent rule as we made on y

[tex]x {}^{ - 2} [/tex]

[tex]x {}^{ - 2} = \frac{1}{x {}^{2} } [/tex]

multiply bot the values we get

Hope it helps!